Implementasi kearifan lokal melalui model bcct untuk pengembangan kemampuan sosial anak usia dini - Wahyuningsih, Dian; Suyanto, Slamet (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2015)
Penelitian ini bertujuan untuk mengetahui perkembangan sosial anak usia dini melalui implementasi kearifan lokal dalam kegiatan bermain model BCCT. Jenis penelitian ini adalah penelitian kualitatif dengan pendekatan fenomenologi. Subjek dalam penelitian adalah perkembangan sosial anak usia 5-6 tahun.Teknik pengumpulan data yang digunakan teknik wawancara dan obser-vasi model event recording. Teknis analisis data yang digunakan adalah analisis induktif model Creswell. Hasil penelitian menunjukkan bahwa nilai kearifan lokal meliputi: (1) rasa syukur, tidak sombong, tidak keras kepala, kebersamaan, berpikir kritis, cermat, legowo, silaturahmi, kesabaran, ketelitian, kreativitas, produk lokal, tata karma (unggah-ungguh); (2) nilai kearifan lokal tersebut terimplementasi melalui lagu tradisional, permainan, lingkungan sekitar, makanan, pakaian, serta bahasa jawa; (3) perkembangan sosial anak yaitu kooperasi, toleransi, empati, memahami lingkung-an sekitar, memahami diri sendiri, dan bersahabat; (4) perilaku sosial dalam bermain anak berubah dari tahap asosiatif menjadi tahap kooperatif pada sentra persiapan, balok, bahan alam, main pe-ran, pasir-air, dan sentra eksplorasi. Dengan demikian TK dapat menggunakan nilai-nilai kearifan lokal untuk mengembangkan kemampuan sosial pada AUD melalui BCCT yang dirancang khusus.Kata kunci: kearifan lokal, BCCT, Perkembangan sosial. The Implementation of Local Wisdom Through BCCT Model for Promoting Social Development of Early Childhood Abstract This study aims to reveal the social development of early childhood through the implemen-tation of local wisdom embodid in the play of children through the BCCT model. This research was a descriptive qualitative research with a phenomenology approach by describing each pheno-menon which appears in the field. The subjects in this study were children’s developments of the age of 5-6 years. The technique of data analysis was the inductive model of Creswell. The results shows that the values of local wisdom introduced to children include: (1) to be grateful, to be happy, to be always happy, to not be arrogant, to not be stubborn, to be confident, to make other people happy, to do the tasks and responsibilities as humans, to show togetherness, to think critically, to be careful, to be sincere (legowo), to keep good relation (silaturahmi), to respect events in the past, to be patient, to be meticulous, to be creative, to respect local are products and to maintain good etiquettes (unggah-ungguh); (2) The values of local implemented through traditional songs, traditional games, historical places and the surroundings, traditional food, clothing, as well as the Javanesse; (3) The social development of the child are cooperative, tolerance, empathy, understanding the environment, understanding oneself, and friendship in the play activities of children continued to increase in in four months during the research; (4) there are changes in the social behaviors of the children, which are from the stage of associative play to the stage of cooperative play shown in the activities including preparation, blocks, natural materials, socio drama, sand-water and exploration; (5) the integration process of local wisdom values with BCCT and social development in the process of playing can instill positive characters since young. Thus, kindergarten can use the values of local wisdom to develop social skills in early childhood through a special designed of BCCT.Keywords: local wisdom, BCCT, social development